2008
DOI: 10.1074/jbc.m800217200
|View full text |Cite
|
Sign up to set email alerts
|

Function and Structure of a Prokaryotic Formylglycine-generating Enzyme

Abstract: Type I sulfatases require an unusual co-or post-translational modification for their activity in hydrolyzing sulfate esters. In eukaryotic sulfatases, an active site cysteine residue is oxidized to the aldehyde-containing C ␣ -formylglycine residue by the formylglycine-generating enzyme (FGE). The machinery responsible for sulfatase activation is poorly understood in prokaryotes. Here we describe the identification of a prokaryotic FGE from Mycobacterium tuberculosis. In addition, we solved the crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 36 publications
(48 reference statements)
3
93
0
2
Order By: Relevance
“…4), suggesting that growth on these substrates stimulates sulfatase expression. Under these conditions, the mutant did not exhibit sulfatase activity, demonstrating that it cannot catalyze maturation of the expressed enzymes (12). These results support that B. thetaiotaomicron has no alternative pathways to activate sulfatases except through anSME.…”
Section: Identification Of Putative Sulfatases In Bacteroidessupporting
confidence: 68%
See 2 more Smart Citations
“…4), suggesting that growth on these substrates stimulates sulfatase expression. Under these conditions, the mutant did not exhibit sulfatase activity, demonstrating that it cannot catalyze maturation of the expressed enzymes (12). These results support that B. thetaiotaomicron has no alternative pathways to activate sulfatases except through anSME.…”
Section: Identification Of Putative Sulfatases In Bacteroidessupporting
confidence: 68%
“…The following antibiotics were added as required: erythromycin (25 g ml Ϫ1 ), gentamicin (200 g ml Ϫ1 ), and 5-fluoro-2-deoxyuridine (200 g ml Ϫ1 ). Minimal medium (MM) consisted of 100 mM KH 2 PO 4 (pH 7.2), 15 mM NaCl, 8.5 mM (NH 4 ) 2 SO 4 , 4 mM L-cysteine, and 10 mg hemin (prepared as a 1000ϫ stock solution in 0.5 M NaOH), 100 M MgCl 2 , 1.4 M FeCl 3 , and 50 M CaCl 2 , 1 g ml Ϫ1 vitamin K 3 and 5 ng ml Ϫ1 vitamin B 12 . Heparin, chondroitin sulfate from shark cartilage, and mucin from porcine stomach (type III) were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In bacteria, two distinct systems have been described for the posttranslational modification of sulfatase enzymes. In Mycobacterium tuberculosis, the conversion of the Cys 58 residue to FGly is catalyzed by an FGly-generating enzyme (FGE), which requires oxygen as a cofactor (45). In Klebsiella pneumoniae, the conversion of the Ser 72 residue of the atsA-encoded sulfatase is catalyzed by the AtsB enzyme, which is a member of the S-adenosyl-L-methionine (AdoMet)-dependent family of radical enzymes (43,46).…”
mentioning
confidence: 99%
“…Interestingly, prokaryotic FGE from Streptomyces coelicolor, which lacks the N-terminal extension, when expressed in the cytoplasm of eukaryotic cells was shown to possess FGly-generating activity acting on engineered cytosolic model substrates containing the FGly modification signature (34,35). On the other hand, we have shown that N-terminally truncated human FGE, when expressed in the ER, did not possess FGly-generating activity, which agrees with the hypothesis that N-terminal processing irreversibly abrogates ER-based FGE functioning.…”
Section: Fge As a Noncanonical Substrate For Furin And Other Pcs-mentioning
confidence: 99%